The ROLE OF EMPLOYEE ENGAGEMENT IN MEDIATING TRANSFORMATIONAL LEADERSHIP, LECTURER COMPETENCE, AND FINANCIAL COMPENSATION ON CAREER SATISFACTION OF LECTURERS AT PRIVATE INSTITUTIONS IN SOUTH SUMATRA (POLITEKNIK LP3I JAKARTA, 2026)
ABSTRACT This study aims to examine the effects of Transformational Leadership, Lecturer Competence, and Financial Compensation on Career Satisfaction through Employee Engagement among lecturers at private institutes in South Sumatra. This study employed a quantitative explanatory approach with a cross-sectional design. The population consisted of 314 permanent lecturers from nine private institutes under LLDIKTI Region II, with saturated sampling employed. Data were collected using a five-point Likert-scale questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results indicate that Transformational Leadership, Lecturer Competence, and Financial Compensation have positive and significant effects on Employee Engagement and Career Satisfaction. Employee Engagement also has a positive and significant effect on Career Satisfaction. Furthermore, Employee Engagement significantly mediates the relationships between Transformational Leadership, Lecturer Competence, Financial Compensation, and Career Satisfaction. These findings imply that improving lecturers’ Career Satisfaction requires effective leadership, adequate competence, fair financial compensation, and stronger Employee Engagement. The study highlights Employee Engagement as an important mechanism linking organizational and individual resources to lecturers’ Career Satisfaction in private higher education institutions. Keywords: Transformational Leadership; Lecturer Competence; Financial Compensation; Employee Engagement; Career Satisfaction; Higher Education.